Effects of and Potential Interventions to Combat Climate Change Impacts on Groundwater Resources in Long Island and Shelter Island - Boughton, Carolanne (Consilience, 2021)
Climate change is predicted to increase the temperature, precipitation, and sea level in the northeastern United States. For coastal communities, these impacts present challenges to maintaining the necessary quantity and quality of groundwater resources. On Long Island and Shelter Island, groundwater is the main source of freshwater for public supply, industrial uses and agriculture. This groundwater is recharged solely from precipitation that percolates into the unconfined aquifers below the ground. A growing population, increased development and urbanization, an expanding sewer system, and more intense storm events all pose threats to the regional groundwater recharge. Data from the Timescale decomposition tool, developed by the International Research Institute for Climate and Society (IRI), substantiate a regional trend of warmer temperatures and increased precipitation. Climate change will likely alter the behavior of climate modes, including the Pacific Decadal Oscillation (PDO), East Pacific/North Pacific (EP/NP) patterns, and Pacific El Niño that impact the Long Island Sound region. Data from the KNMI Climate Explorer underscore a connection between PDO and land/sea global mean temperature, as well as El Niño and sea surface temperature anomalies. New York State has developed a water conservation policy concerning well-pumping practices and groundwater effluent standards. Long Island counties have also set local water management goals to improve wastewater treatment, enhance aquifer protection, and increase the transparency and availability of pumping records. These goals must be enforced and actualized. This paper recommends that Shelter Island develop a groundwater management plan like those in place throughout Long Island. The islands are advised to consider innovative water storage strategies such as Aquifer Storage and Recovery (ASR), Artificial Recharge (AR), and rainwater harvesting. These practices, along with land use and urbanization planning, will help promote local resilience and groundwater resource sustainability. Further modeling of local groundwater dynamics and enhanced knowledge of pumping practices are necessary to develop more accurate predictions of the groundwater system under future climate scenarios.